Ethnobotanical survey of Artemisia vulgaris and Laurus nobilis in the Treatment of Microbial Gastroenteritis in Northwestern Tunisia - Tabouii, Marwa; Mahmoudi, Hela; Aouadhi, Chedia (Ethnobotany Research and Applications, 2026)
Background: Microbial gastroenteritis remains a major public health concern, particularly in regions where hygiene conditions and access to healthcare are limited. Alongside conventional treatments, medicinal plants are widely used in traditional medicine to manage gastrointestinal infections. However, community knowledge, perceptions, and practices regarding their use remain insufficiently documented. Understanding these aspects is essential to support the rational integration of traditional remedies into modern healthcare. Methods: A cross-sectional ethnobotanical survey was conducted among 100 participants from diverse socio-professional backgrounds. Data were collected using a structured questionnaire covering sociodemographic characteristics, awareness of microbial gastroenteritis, perceived causes and symptoms, treatment preferences, and knowledge of medicinal plants used for gastrointestinal disorders. Descriptive analysis was performed to identify trends in perceptions and practices related to plant-based therapies. Results: The study population was predominantly female (72%), with a mean age of 32.5 years. Awareness of microbial gastroenteritis was high (94%), with poor hygiene and bacterial contamination identified as the main causes. Diarrhea, abdominal pain, and vomiting were the most frequently reported symptoms. Medicinal plants were the preferred treatment option for 52% of respondents, while 24% combined herbal remedies with antibiotics. Nearly half of the participants had previously experienced microbial gastroenteritis, with a higher prevalence among women. Most respondents perceived medicinal plants as effective and safe, as 91% reported no adverse effects. Artemisia vulgaris and Laurus nobilis were the most recognized species (89%), and infusion was the most common preparation method (86.6%). Conclusion: The findings reveal a strong reliance on medicinal plants for managing microbial gastroenteritis and generally positive perceptions of their efficacy and safety. These results emphasize the need for further pharmacological and clinical studies to validate the therapeutic potential of commonly used plants and support their integration into evidence-based medical practice. Keywords: Ethnobotanical survey; Medicinal plants; Microbial gastroenteritis; Traditional medicine; Artemisia vulgaris; Laurus nobilis